2007
DOI: 10.1371/journal.pmed.0040283
|View full text |Cite
|
Sign up to set email alerts
|

Physician Awareness of Drug Cost: A Systematic Review

Abstract: BackgroundPharmaceutical costs are the fastest-growing health-care expense in most developed countries. Higher drug costs have been shown to negatively impact patient outcomes. Studies suggest that doctors have a poor understanding of pharmaceutical costs, but the data are variable and there is no consistent pattern in awareness. We designed this systematic review to investigate doctors' knowledge of the relative and absolute costs of medications and to determine the factors that influence awareness.Methods an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

18
217
4
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 245 publications
(245 citation statements)
references
References 60 publications
18
217
4
6
Order By: Relevance
“…Hernu et al [3] report results similar to those found in other European countries [4,5]. They also present two clinical situations (septic and haemorrhagic shock) showing how relevant the differences can be between estimated and true costs at ICU, regional, and national level.The lack of any improvement in physicians' awareness of the costs of drugs over time [2,3] agrees with the slow and continuous decrease in the percentage of articles in …”
mentioning
confidence: 67%
See 4 more Smart Citations
“…Hernu et al [3] report results similar to those found in other European countries [4,5]. They also present two clinical situations (septic and haemorrhagic shock) showing how relevant the differences can be between estimated and true costs at ICU, regional, and national level.The lack of any improvement in physicians' awareness of the costs of drugs over time [2,3] agrees with the slow and continuous decrease in the percentage of articles in …”
mentioning
confidence: 67%
“…The lack of any improvement in physicians' awareness of the costs of drugs over time [2,3] agrees with the slow and continuous decrease in the percentage of articles in…”
mentioning
confidence: 67%
See 3 more Smart Citations